Lithium in the treatment of bipolar disorder: pharmacology and pharmacogenetics - Alda, M (Molecular psychiatry, 2015)
After decades of research, the mechanism of action of lithium in preventing recurrences of bipolar disorder remains only partially understood. Lithium research is complicated by the absence of suitable animal models of bipolar disorder and by having to rely on in vitro studies of peripheral tissues. A number of distinct hypotheses emerged over the years, but none has been conclusively supported or rejected. The common theme emerging from pharmacological and genetic studies is that lithium affects multiple steps in cellular signaling, usually enhancing basal and inhibiting stimulated activities. Some of the key nodes of these regulatory networks include GSK3 (glycogen synthase kinase 3), CREB (cAMP response element-binding protein) and Na(+)-K(+) ATPase. Genetic and pharmacogenetic studies are starting to generate promising findings, but remain limited by small sample sizes. As full responders to lithium seem to represent a unique clinical population, there is inherent value and need for studies of lithium responders. Such studies will be an opportunity to uncover specific effects of lithium in those individuals who clearly benefit from the treatment.
Keywords: Humans; farmakogenetika; bipolární porucha; Lithium Compounds; sloučeniny lithia; Pharmacogenetics; Bipolar Disorder; Antimanic Agents; antimanika; lidé